1966
DOI: 10.1039/df9664100328
|View full text |Cite
|
Sign up to set email alerts
|

Studies of cations in zeolites: adsorption of carbon monoxide; formation of Ni ions and Na 3+ 4 centres

Abstract: Zeolite cations lying on the intracrystalline pore surface of the Linde X and Y molecular sieves are linked to only three oxide ions and consequently are not well shielded electrically. They therefore create very large electrostatic fields, extending into the main zeolitic cavities, causing carboniogenic catalytic activity. This activity follows in magnitude the changes in the field, and is independent of the presenceof OH groups ; nochange in activity is observedeven after 99 %of OH protons present after ordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
0
3

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(124 citation statements)
references
References 1 publication
6
115
0
3
Order By: Relevance
“…Of particular interest is that the intermediate paramagnetic charge state nickel(I) can be stabilized in zeolite lattices and also on silica surfaces [22][23][24][25][26][27]. Photoreduction of nickel(II) by ultraviolet light under molecular hydrogen at low temperature has been used to generate the intermediate nickel(I) but this method is rather inefficient and is not used very much.…”
Section: Nickel Species In Zeolitesmentioning
confidence: 99%
“…Of particular interest is that the intermediate paramagnetic charge state nickel(I) can be stabilized in zeolite lattices and also on silica surfaces [22][23][24][25][26][27]. Photoreduction of nickel(II) by ultraviolet light under molecular hydrogen at low temperature has been used to generate the intermediate nickel(I) but this method is rather inefficient and is not used very much.…”
Section: Nickel Species In Zeolitesmentioning
confidence: 99%
“…1 There have been several studies on Na clusters generated in zeolites with the FAU-type structure. Rabo et al [7] exposed Na-type Y (Na-Y) to the Na vapor and observed ESR signal originated from Na 4 3 + clusters generated in the b cages, where one guest 3 s-electron was shared by 4 Na + ions. Harrison et al [8] observed the narrowing of the ESR signal in highly Na-loaded Na-Y and suggested the motional narrowing mechanism.…”
Section: Introductionmentioning
confidence: 98%
“…By the second method alkali metal clusters are produced in the zeolite cavities [8]. The method of metal introduction used in the practice are as follows: treatment in alkali metal vapour generated by evaporation of the alkali metal or decomposition of alkali metal azide furthermore, deposition of alkali metal or its complex from solution of ammonia or naphtalene containing tetrahydrofurane.…”
Section: Basicity Testmentioning
confidence: 99%